(untitled) (Journal of the Bangladesh Agricultural University, 2024)
The study was carried out to examine participation of women in small ruminant rearing and household decision making process at Banshkhali Upazila in Chattogram. Four villages were purposively selected based on the density of small ruminant rearing. Data were collected from 50 households using random sampling method with a structured questionnaire. Descriptive statistic, Participation Index and Logistic Regression Analysis were used to analyse the data. The results of the study showed that (36%) young women were engaged in small ruminant rearing (26-35 age group) and major proportion of the respondents (46%) in the study areas were primary educated. About 52% of the respondents have a family size consisting of 6-10 members. Nearly half (46%) of the women involved in rearing small ruminants earned between BDT 12,000.00 - BDT 18,000.00 per annum. The participation index implies that large proportions of women were always participating in supplying water, feeding and providing fodder and cleaning barns/corrals/pens of small ruminants. Moreover, they were rarely participating in construction of house/barns/corrals/pens, rearing in confinement/partial-confinement/free ranges system and bringing animal to veterinary surgeon for vaccination purpose. In household condition, women involved in decision making for rearing livestock, marriage of children whereas rarely participate in activities such as selection of variety and inputs for agricultural production, education of children, purchase of household assets and have minimal participation in selling household assets, freedom of mobility. A logistic regression analysis revealed that women’s participation in household decision making process was negatively related with family size and farm size, but positively related with respondent’s income (P<0.05) and education (P<0.01). It may be concluded that higher the education and income of women, more the tendency of making household decisions alone. J Bangladesh Agril Univ 19(1): 128–133, 2021 https://doi.org/10.5455/JBAU.26333